Antibacterial, Antidiabetic, Antioxidant and DNA cleavage studies of novel N(3-(bis(pyridine-2ylmethyl)amino)-2-hydroxypropyl) benzene sulphonamide ligand (Romanian Biotechnological Letters, 2024)
The novel N (3-(bis(pyridine-2ylmethyl)amino)-2-hydroxypropyl) benzene sulphonamide ligand have been synthesized from 1,3-Diamino-propan-2-ol. The structure of the ligand was confirmed by Mass spectroscopy and 1H NMR spectroscopy. The synthesized Schiff base ligand was tested for their in vitro anti bacterial action with Gram-positive and negative bacteria. The anti-diabetic activities have been tested with α-amylase inhibition method and antioxidant effect of the compound was established using DPPH method. Thus all the studies reveals that the synthesised Schiff base compound has significant antibacterial, antidiabetic and antioxidant activities. The DNA cleavage studies shown that, the DNA binding nature of the ligand was appreciably good. The Molecular docking characteristics were supported that the binding approach of the effective inhibitors with the active site of enzymes.
Keywords: sulphonamide; antibacterial; antidiabetic; antioxidant; DNA cleavage and stability